Values Behind Circular Consumption - A Comparison Between Thailand and Laos - Sengsouly, Homedahack; Sasne Grosz, Annamaria (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2025)
Purpose – The Authors investigate how open consumers are in Thailand and Laos for consumption solutions of fashion products supporting the circular economy and what the relationships are between their behavior and cultural values; additionally, they compare the characteristics of the two countries’ respondents. Design – The study utilizes a quantitative approach. Based on the literature background, a questionnaire was compiled and completed by 62 respondents from Laos and Thailand. Findings – The study’s findings are based on correlation analysis of the Schwartz value set and circular economy-related issues, including openness to circular economy, switching behavior for sustainable fashion solutions (remanufactured and second-hand products), and a Welch test comparing respondents’ answers from Laos and Thailand. Results show that, despite close similarities in culture and values, the openness of Thai and Lao respondents to circular economy is different from each other, and they also prefer different circular solutions in the field of fashion consumption. Research limitations – the selection of participants and the small number of respondents. Practical implications – By highlighting similarities and differences between Laos and Thailand, practical implications include the possibility of using this information to choose an appropriate form of fashion products for the Lao market, thereby supporting circular economy-related behavior. Originality/value – This work is one of the first attempts to discover Lao people’s opinion about circular economy supporting behavior related to fashion products.